2011
DOI: 10.4028/www.scientific.net/amr.175-176.646
|View full text |Cite
|
Sign up to set email alerts
|

Research on Polypropylene Dyeing in Supercritical Carbon Dioxide

Abstract: Polypropylene fibers were dyed with Disperse dyes Blue 2B in Supercritical Carbon Dioxide at different temperature, pressure and time. The K/S value were determined and the effect of as temperature, pressure and dyeing time on the dyeing behaviours of disperse dyes on Polypropylene fibers were discussed. It was found that with the increase of dyeing temperature and pressure, the K/S value increased gradually, and dyeing effect was best after the fiber was dyed at 120 °C, 28 MPa for 20 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Studies on PP dyeing in an aqueous system showed that dyestuffs with higher hydrophobicity than those commonly used for PET dyeing are required . Therefore, supercritical dyeing of PP could be a suitable alternative . Tests with different classes of disperse dyes were performed and it was found that the dyeability of PP improved when both the hydrophobicity and aliphaticity of the dye were high .…”
Section: Supercritical Dyeing Of Other Synthetic Fibresmentioning
confidence: 99%
“…Studies on PP dyeing in an aqueous system showed that dyestuffs with higher hydrophobicity than those commonly used for PET dyeing are required . Therefore, supercritical dyeing of PP could be a suitable alternative . Tests with different classes of disperse dyes were performed and it was found that the dyeability of PP improved when both the hydrophobicity and aliphaticity of the dye were high .…”
Section: Supercritical Dyeing Of Other Synthetic Fibresmentioning
confidence: 99%
“…A total of 386 data sets on experimental dyeing belonging to 14 groups collected from the published papers are used for training the GRNN and BPNN models, the selected 3 to 4 data sets in each group are used for testing and prediction and the rest are used for training. The training, testing and prediction data collected from references [29][30][31][32][33][34][35] are shown in Table 1 and the detailed data were added in the file of "Supplementary File 1". Two of the five variables of temperature, pressure, dye stuff types, carrier types and dyeing time were employed as the influencing factors and K/S value or dye-uptake were selected as performance indexes.…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%